2020
DOI: 10.9770/jesi.2020.7.3(11)
|View full text |Cite
|
Sign up to set email alerts
|

Modeling cryptocurrencies volatility using GARCH models: a comparison based on Normal and Student's T-Error distribution

Abstract: This study measures the volatility of cryptocurrency by utilizing the symmetric (GARCH 1,1) and asymmetric (EGARCH, TGARCH, PGARCH) model of GARCH family using a daily database designated in different digital monetary standards. The results for an explicit set of currencies for entire period provide evidence of volatile nature of cryptocurrency and in most of the cases, the PGARCH is a better-fitted model with student's t distribution. The findings show positive shocks heavily affected conditional volatility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…After taking the first differences, both conditional series have shown a 1 and 5% level of significance for all variables. The last column has contained the order of integration in which I represent the integrated order of variables (Johansen, 1992;Cheung and Lai, 1995;Mohsin et al, 2020a;Salamat et al, 2020). The numeric values 0 and 1 are used for level and first difference.…”
Section: Resultsmentioning
confidence: 99%
“…After taking the first differences, both conditional series have shown a 1 and 5% level of significance for all variables. The last column has contained the order of integration in which I represent the integrated order of variables (Johansen, 1992;Cheung and Lai, 1995;Mohsin et al, 2020a;Salamat et al, 2020). The numeric values 0 and 1 are used for level and first difference.…”
Section: Resultsmentioning
confidence: 99%
“…Again, the fake news of social media restricted the general public from accepting the vaccine of COVID-19. The useful information and encouraging vaccine material are rare on social media than negative and discoursing materials (Salali and Uysal, 2020;Madison et al, 2021;Murphy et al, 2021). Hence, we proposed the following hypothesis:…”
Section: Moderating Role Of Covid-19 Vaccinementioning
confidence: 99%
“…Frenkel et al (2020) indicated that once the WHO complained that social media organizations have been spreading false information over COVID-19 worldwide; few social media groups used their platforms to spread incorrect data and tried to remove it. A recent study described the effect of media on the health of people ( Mohsin et al, 2020b ; Salamat et al, 2020 ; Naseem et al, 2021 ; Sarfraz et al, 2021 ). Muwahed (2020) stated that social media had affected the shocking crisis over some countries while many people have been greedy for buying foodstuff and household things because of the widespread fear of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, among several unique properties, [40] found that cryptocurrencies have leverage effects and Student's t error distributions. The study [41] uses the symmetric (GARCH 1,1) and asymmetric (EGARCH, TGARCH and PGARCH) models to measure the volatility of cryptocurrencies. The results prove again the high volatility of cryptocurrencies and in most cases, the asymmetric PGARCH with Student's t distribution provides a better fit.…”
Section: Data and Criteriamentioning
confidence: 99%